Квалитетот на живот кај жени со цервикална дисплазија предизвикана од Хуманиот папилома вирус - Јовановска, Викторија (Медицински факултет, УКИМ, Скопје, 2018)
Introduction: Quality of life can be defined in different ways, so its measurement and incorporation into clinical studies is difficult. Worldwide are being using multidimensional questionnaires covering multiple segments of life of patients. In Republic of Macedonia there is little data on the quality of life in women with cervical dysplasia caused by human papilloma virus (HPV). The goal of the research is to assess the quality of life in women with cervical dysplasia caused by human papilloma virus, which will highlight the importance of the quality of life of the patients Material and Methods: The research is a prospective sectional study, performed at the University Clinic of Gynecology and Obstetrics - Skopje in the period 10.01.2017 - 31.03.2018 year. Analyzed were 200 patients older than 18 years who had been diagnosed cervical dysplasia caused by human papilloma virus. The required data were collected with a modified questionnaire Joka-2015 consisting of four parts: sociodemographic part, general facts about HPV, effects that affect to the future pregnancies, a questionnaire to assess the quality of life of the patients. Questionnaire to assess quality of life is consisted of 36 questions, grouped into six areas: physical well-being, sexual activity, satisfaction with treatment, general impressions, emotional wellbeing, social relationships. As a measure of internal consistency among the issues of each area an Cronbach’s Alpha has been made. In the analysis of the data the following things are prepared: structure percentages, descriptive statistics, analysis of variance, multi variable regression analysis, Spermanov correlation coefficient rankings. Results: Out of 200 patients, is usually identified to the 45(22,50%) patients a type HPV 16, of whom 15(33,33%) patients is associated with Carcinoma in situ. The quality of life of the patients (average total score) in the six areas varies in the interval: physical well-being (8,78±5,15); sexual activity (9,76±2,79); satisfaction with treatment (13,15±2,94); general impressions (21,13±4,11); emotional wellbeing (20,12±9,79); social relationships (13,27±2,50); total score of (86,20±13,84). For R=0,53 and p<0,001 it is set a medium strong significant correlation between general impressions as a dependent occurrence and social (B=0,41), sexual activity (B=0,32), physical well-being (B=-0,15), emotional wellbeing (B=-0,07), satisfaction with treatment (B=0,21). For R=0,40 и p<0,001 it is set a moderately strong significant correlation between the sexual activity as dependent occurrence and physical well-being (B=0,19), satisfaction with treatment (B=0,19), sexual activity (B=-0,05). For R=0,52 and p<0,001 it is set a medium strong significant correlation between social ties as dependent occurrence and general impressions (B=0,15), emotional wellbeing (B=-0,06), sexual activity (B=0,13), physical well-being (B=-0,07), satisfaction with treatment (B=0,12). Conclusion: The high values for Cronbach’s Alpha pointed to strong internal consistency among the issues of each area of the questionnaire, which enabled determination of relevant values of the total score for an objective assessment of the quality of life of the patients. It is found a significant correlation between individual areas of the questionnaire.
Quality of life in women with cervical dysplasia caused by Human papilloma virus
Докторска дисертација одбранета во 2018 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Никола Оровчанец.
Keywords: HPV, Cronbach's Alpha, quality of life